If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11y + -4 = 40 Reorder the terms: -4 + 11y = 40 Solving -4 + 11y = 40 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 11y = 40 + 4 Combine like terms: -4 + 4 = 0 0 + 11y = 40 + 4 11y = 40 + 4 Combine like terms: 40 + 4 = 44 11y = 44 Divide each side by '11'. y = 4 Simplifying y = 4
| -3-3n=-n+3 | | ln(x+-3)+ln(x+2)=ln(x+-7) | | 1/5x+5h-1/5x | | -4m-13=5-m | | 6k+2=16+4k | | x+2=-68 | | 26=2x-14 | | (9i+11i)/10i | | Y-x=4x^2-8 | | -3-8x+7x=-3+5x | | 14=8z+6 | | log(7)16807=y | | 12m-71=25 | | 8p+4p+6=3p+7p | | 2x-x-3=5 | | 5b(b+4c)= | | x^2+0x+14=0 | | 247=-v+5(6v+3) | | 4y-9=27 | | 6(-1-6x)=246 | | 21/3=m/42 | | -343=-8(7-7a) | | 5(x-1)=5(4x-3) | | s^13t^8/s^2t | | 0=24x^2+28x-24 | | 3n+1=4n-2 | | -5(1-5x)+5x(-8x-2)=-4x-8x | | 24/15=20 | | 36=(6x+1)/(x-6) | | X^2-5x-36=4x | | X^3=-2x^2+8x | | (X+5)/4=-7 |